THE DESIGN OF TOOLS AND LOCATION DETERMINATION FOR THE VISUALLY IMPAIRED USES A MICROCONTROLLER-BASED ULTRASONIC SENSOR - Mulkan Iskandar Nasution; Syahrul Ardiansyah (Universitas Islam Negeri Sumatera Utara Medan, 2020)
....